2002
DOI: 10.1259/bjr.75.890.750140
|View full text |Cite
|
Sign up to set email alerts
|

A method to obtain the same levels of CT image noise for patients of various sizes, to minimize radiation dose

Abstract: The aim of this study was to develop a method of obtaining the same levels of CT image noise for patients of various sizes to minimize radiation dose. Two CT systems were evaluated regarding noise characteristics using phantoms and dosimetric measurements. Both CT systems performed well at dose levels used in normal clinical imaging, but only one was found to be suitable for low radiation dose applications. The CT system with the lowest noise level was used for further detailed studies. A simple strategy for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 20 publications
2
51
1
Order By: Relevance
“…In this study, the dose efficacy concept was introduced and used at a level of 0.5 HU mGy −1 on the basis of results obtained from the Rose model observer. It appears that for the unit and slice thickness investigated this dose efficacy leads to an image noise level of about 10 HU for children weighing 839 [30], this corresponds to images of very good quality, since images with a standard deviation of 10 HU were considered of high quality whereas images with a standard deviation of 30 HU were considered very noisy. Thus, the dose levels proposed in this paper can be reduced when image quality requirements are not particularly high.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, the dose efficacy concept was introduced and used at a level of 0.5 HU mGy −1 on the basis of results obtained from the Rose model observer. It appears that for the unit and slice thickness investigated this dose efficacy leads to an image noise level of about 10 HU for children weighing 839 [30], this corresponds to images of very good quality, since images with a standard deviation of 10 HU were considered of high quality whereas images with a standard deviation of 30 HU were considered very noisy. Thus, the dose levels proposed in this paper can be reduced when image quality requirements are not particularly high.…”
Section: Discussionmentioning
confidence: 98%
“…The tube voltage was 120 kV. Slice thickness and tube current were set according to a dose reduction scheme (15). Precision errors were calculated from double determinations: subcutaneous adipose tissue (0.5%) and the sum of intraperitoneal and retroperitoneal adipose tissue areas (intra-abdominal adipose tissue area; 1.2%).…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, it has been recently shown that there is possibility to gather goodquality images with a decreased tube voltage by increasing iodine absorption when the heart is exposed to a lower voltage. [26][27][28] CONClUsION Cardiac computed tomography is reliable imaging method, which has grown rapidly in the last decade and continues to develop in order to achieve what patients and clinicians are looking for -the best decision-making process in terms of diagnosis. However, these improvements also bring side effects, which have to be managed judiciously by clinicians, radiology engineers, and manufacturers.…”
Section: Tube Voltagementioning
confidence: 99%